Preparation method of high-strength heat-resistant polymethacrylimide foam
By using crosslinking agents such as ethylene glycol dimethacrylate to prepare high-strength heat-resistant polymethacryimide foam, the problems of high cost and poor performance of PMI foam materials are solved, and the mechanical properties and heat resistance are improved.
Patent Information
- Application Number
- CN202311711947.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-13
- Publication Date
- 2025-07-22
AI Technical Summary
The existing PMI foam materials are expensive due to the high price of methacrylonitrile, which leads to high foam prices and poor mechanical properties and heat resistance at low density, and the commonly used foaming agent formamide is highly toxic.
High-strength heat-resistant polymethacrylamide foam is prepared by prepolymerization, casting polymerization, foaming and heat treatment to form a crosslinking structure to improve the mechanical and heat resistance of the copolymer.
It effectively reduces the cost of PMI foam, improves its mechanical properties and heat resistance, and avoids the toxicity problem of traditional foaming agents.
Smart Images

Figure CN120349452A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing polymethacrylimide foam. Background Art
[0002] Polymethacrylimide (PMI) refers to a copolymer with a six-membered imide ring structure, which is a copolymer prepared by free radical polymerization of methacrylic acid monomers and methacrylonitrile monomers. Under high temperature and pressure, the polymer undergoes an imide cyclization reaction with amine compounds or adjacent groups in the polymer chain to form a six-membered imide ring structure.
[0003] Currently, there are still some problems in the field of PMI foam. For example, due to the high price of the raw material methacrylonitrile, the price of PMI foam has been kept high; the formamide foaming agent has good foaming effect, but it is highly toxic and needs to find a substitute; at the same time, the research group where the inventor is located has carried out some preliminary work. By testing PMI foams with different densities, it is found that when the density of PMI foam decreases, its mechanical properties and heat resistance decrease significantly.
[0004] Therefore, it is necessary to find a method for preparing high-strength and heat-resistant polymethacrylimide foam. Summary of the Invention
[0005] The purpose of the present invention is to solve the problems that the PMI foam prepared by the existing method using methacrylonitrile is expensive and the mechanical properties and heat resistance of PMI foam with low foam density are poor, and to provide a method for preparing high-strength and heat-resistant polymethacrylimide foam.
[0006] A method for preparing high-strength and heat-resistant polymethacrylimide foam is specifically completed according to the following steps:
[0007] I. Weighing materials:
[0008] Weigh 40 to 50 parts by weight of butyl methacrylate, 45 to 55 parts by weight of acrylamide, 1 to 3 parts of crosslinking agent, 2 to 5 parts of foaming agent, and 0.2 to 0.3 parts of initiator to obtain raw materials;
[0009] The crosslinking agent described in step I is ethylene glycol dimethacrylate, allyl methacrylate or triallyl isocyanurate;
[0010] The foaming agent described in step I is urea and ammonium carbonate, and the mass ratio of urea to ammonium carbonate is 3:1;
[0011] II. Prepolymerization:
[0012] Place the raw materials in a high-temperature water bath at 80 - 95 °C for prepolymerization for 5 - 30 minutes to obtain a prepolymerized system;
[0013] III. Polymerization:
[0014] The pre-polymerized system is cast into a closed mold with nitrogen protection by the casting method, and then the mold is placed in a constant temperature water bath for polymerization for 45 h to 50 h. The water bath temperature is controlled at 40 °C to 60 °C. The mold is removed to obtain a transparent copolymer resin sheet.
[0015] IV. Foaming:
[0016] The transparent copolymer resin sheet is placed in a flat vulcanizing machine at 180 - 200 °C for foaming for 30 min to 60 min to obtain a foam material.
[0017] V. Heat treatment:
[0018] The foam material is placed in a high-temperature oven at 200 °C to 280 °C for heat treatment for 8 h to 24 h, and then naturally cooled to room temperature to obtain high-strength heat-resistant polymethacrylimide foam.
[0019] Advantages of the present invention:
[0020] I. Since butyl methacrylate (BMA) and acrylamide (AM) cannot undergo ideal alternating copolymerization, the imidization reaction is difficult to occur during heat treatment, and the imidization ratio is low. Although the copolymer composition can be effectively controlled by adjusting the monomer ratio during feeding, when AM reacts completely, homopolymer linear segments of BMA will appear in the copolymer, which is not conducive to the mechanical properties of the final foam. Therefore, it is necessary to add a cross-linking agent to cross-link the linear segments to achieve a modification effect equivalent to imidization. Therefore, the present invention synthesizes PMI foam using ethylene glycol dimethacrylate (EGDMA), allyl methacrylate (AMA), and triallyl isocyanurate (TAIC) as cross-linking agents.
[0021] II. The present invention first performs pre-polymerization in a high-temperature water bath at 80 - 95 °C, and then performs low-temperature polymerization in a water bath at 40 °C to 60 °C. The reason is that: the system cannot continue to react at high temperature, otherwise, as the reaction continues, the viscosity of the system will increase rapidly, the reaction heat cannot be removed in time, and the system will undergo explosive polymerization. Therefore, when the system reaches a certain viscosity, it is necessary to quickly transfer the polymerization system to the polymerization mold by the casting method for polymerization.
[0022] III. The present invention uses ethylene glycol dimethacrylate, allyl methacrylate, and triallyl isocyanurate as cross-linking agents, connecting the regions where the six-membered imide ring is not formed into a cross-linked network-like three-dimensional structure, which can greatly improve the mechanical and heat-resistant properties of the copolymer foam.
[0023] IV. The present invention effectively solves the problem that the high price of raw material methylacrylonitrile leads to the high price of PMI foam all the time. The present invention also solves the shortcoming that the common foaming agent formamide has high toxicity. Description of the Drawings
[0024] Figure 1 It is the partial imidization reaction formula of butyl methacrylate and acrylamide in Comparative Example 1;
[0025] Figure 2 It is the infrared spectrogram of the BMA / AM copolymer foam prepared in Comparative Example 1 before and after heat treatment, (a) before heat treatment, (b) after heat treatment;
[0026] Figure 3 It is the FTIR spectrogram of PMI foams prepared by adding different crosslinking agents. In the figure, (a) is the BMA / AM copolymer prepared in Comparative Example 1 without adding crosslinking agent, (b) is the high-strength and heat-resistant polymethacrylimide foam prepared in Example 1 using EDGMA crosslinking agent, (c) is the high-strength and heat-resistant polymethacrylimide foam prepared in Example 2 using AMA crosslinking agent, and (d) is the high-strength and heat-resistant polymethacrylimide foam prepared in Example 3 using TAIC crosslinking agent;
[0027] Figure 4 It is the PMI molecular chain structure diagram with crosslinked network of the high-strength and heat-resistant polymethacrylimide foam prepared in Example 1 using EDGMA crosslinking agent;
[0028] Figure 5 It is the PMI molecular chain structure diagram with crosslinked network of the high-strength and heat-resistant polymethacrylimide foam prepared in Example 2 using AMA crosslinking agent;
[0029] Figure 6 It is the chemical structural formula of three crosslinking agents used in the present invention;
[0030] Figure 7 It is the digital photo diagram and SEM microstructural diagram of the high-strength and heat-resistant polymethacrylimide foam prepared in Example 1 using EDGMA crosslinking agent. Detailed Embodiments
[0031] Detailed Embodiment 1: A preparation method of a high-strength and heat-resistant polymethacrylimide foam in this embodiment is specifically completed according to the following steps:
[0032] I. Weighing materials:
[0033] Weigh 40 parts to 50 parts of butyl methacrylate, 45 parts to 55 parts of acrylamide, 1 part to 3 parts of crosslinking agent, 2 parts to 5 parts of foaming agent and 0.2 part to 0.3 part of initiator by weight to obtain raw materials;
[0034] The crosslinking agent described in Step 1 is ethylene glycol dimethacrylate, allyl methacrylate or triallyl isocyanurate;
[0035] The blowing agent described in Step 1 is urea and ammonium carbonate, and the mass ratio of urea to ammonium carbonate is 3:1;
[0036] II. Pre-polymerization:
[0037] Place the raw materials in a high-temperature water bath at 80 - 95 °C for pre-polymerization for 5 - 30 minutes to obtain a pre-polymerized system;
[0038] III. Polymerization:
[0039] Adopt the casting method to pour the pre-polymerized system into a closed mold with nitrogen protection, and then place the mold in a constant-temperature water bath for polymerization for 45 - 50 hours. The water bath temperature is controlled at 40 - 60 °C. Remove the mold to obtain a transparent copolymer resin sheet;
[0040] IV. Foaming:
[0041] Place the transparent copolymer resin sheet in a flat vulcanizing machine at 180 - 200 °C for foaming for 30 - 60 minutes to obtain a foam material;
[0042] V. Heat treatment:
[0043] Put the foam material into a high-temperature oven at 200 - 280 °C for heat treatment for 8 - 24 hours, and then naturally cool to room temperature to obtain high-strength heat-resistant polymethacrylimide foam.
[0044] Specific Embodiment 2: The difference between this embodiment and Specific Embodiment 1 is that the initiator described in Step 1 is azobisisobutyronitrile. Other steps are the same as those in Specific Embodiment 1.
[0045] Specific Embodiment 3: The difference between this embodiment and one of Specific Embodiments 1 or 2 is that 45 parts by weight of butyl methacrylate, 50 parts by weight of acrylamide, 2 parts by weight of crosslinking agent, 3 parts by weight of blowing agent and 0.2 parts by weight of initiator are weighed in Step 1. Other steps are the same as those in Specific Embodiment 1 or 2.
[0046] Specific Embodiment 4: The difference between this embodiment and one of Specific Embodiments 1 to 3 is that in Step 2, the raw materials are placed in a high-temperature water bath at 90 - 95 °C for pre-polymerization for 10 - 20 minutes to obtain a pre-polymerized system. Other steps are the same as those in Specific Embodiments 1 to 3.
[0047] Specific Embodiment 5: The difference between this embodiment and any one of Specific Embodiments 1 to 4 is that in Step 2, the raw materials are placed in a high-temperature water bath at 80-90°C for pre-polymerization for 25-30 minutes to obtain a pre-polymerized system. Other steps are the same as those in Specific Embodiments 1 to 4.
[0048] Specific Embodiment 6: The difference between this embodiment and any one of Specific Embodiments 1 to 5 is that in Step 3, the pre-polymerized system is poured into a closed mold with nitrogen protection by the casting method, and then the mold is placed in a constant-temperature water bath for polymerization for 48-50 hours. Other steps are the same as those in Specific Embodiments 1 to 5.
[0049] Specific Embodiment 7: The difference between this embodiment and any one of Specific Embodiments 1 to 6 is that the water bath temperature in Step 3 is controlled at 45-55°C. Other steps are the same as those in Specific Embodiments 1 to 6.
[0050] Specific Embodiment 8: The difference between this embodiment and any one of Specific Embodiments 1 to 7 is that in Step 4, the transparent copolymer resin sheet is placed in a flat vulcanizing machine at 190-200°C for foaming for 50-60 minutes to obtain a foam material. Other steps are the same as those in Specific Embodiments 1 to 7.
[0051] Specific Embodiment 9: The difference between this embodiment and any one of Specific Embodiments 1 to 8 is that in Step 5, the foam material is placed in a high-temperature oven at 240-280°C for heat treatment for 8-16 hours. Other steps are the same as those in Specific Embodiments 1 to 8.
[0052] Specific Embodiment 10: The difference between this embodiment and any one of Specific Embodiments 1 to 9 is that in Step 5, the foam material is placed in a high-temperature oven at 200-240°C for heat treatment for 16-24 hours. Other steps are the same as those in Specific Embodiments 1 to 9.
[0053] The following examples are used to verify the beneficial effects of the present invention:
[0054] Comparative Example 1: The preparation method of BMA / AM copolymer foam is specifically completed according to the following steps:
[0055] I. Weighing materials:
[0056] Weigh 50 parts of butyl methacrylate, 45 parts of acrylamide, 0.2 part of initiator and 3 parts of foaming agent by weight to obtain raw materials;
[0057] The foaming agent described in Step 1 is urea and ammonium carbonate, and the mass ratio of urea to ammonium carbonate is 3:1;
[0058] The initiator described in Step 1 is azobisisobutyronitrile;
[0059] II. Pre-polymerization:
[0060] The raw materials were placed in a high-temperature water bath at 90 °C for 20 min of pre-polymerization to obtain the pre-polymerized system, as shown in Figure 1 the figure;
[0061] III. Polymerization:
[0062] The pre-polymerized system was cast into a closed mold with nitrogen protection by the casting method, and then the mold was placed in a constant-temperature water bath for 45 h of polymerization. The water bath temperature was controlled at 55 °C, and the mold was removed to obtain a transparent copolymer resin sheet;
[0063] IV. Foaming:
[0064] The transparent copolymer resin sheet was placed in a flat vulcanizing machine at 200 °C for 40 min of foaming to obtain a foam material;
[0065] V. Heat treatment:
[0066] The foam material was placed in a high-temperature oven at 240 °C for 16 h of heat treatment, and then naturally cooled to room temperature to obtain the BMA / AM copolymer foam.
[0067] Figure 1 It is the reaction formula of the partial imidization of butyl methacrylate and acrylamide in Comparative Example 1;
[0068] From Figure 1 it can be seen that: under high-temperature treatment, the amide reacts with the adjacent ester group in this linear prepolymer to form an imide ring and generate n-butanol as a by-product; after heat treatment, the infrared spectrum is shown in Figure 2 the figure;
[0069] Figure 2 It is the infrared spectrum of the BMA / AM copolymer foam prepared in Comparative Example 1 before and after heat treatment, (a) before heat treatment, (b) after heat treatment;
[0070] From Figure 2 it can be seen that: after heat treatment, in the copolymer of BMA / AM, the characteristic ester group peaks at 1721 cm -1 , 1270 cm -1 , 1240 cm -1 and 1146 cm -1 significantly weaken, and the ester group of the BMA link in the copolymer has reacted. Moreover, the C=O stretching vibration peak of the AM link at about 1664 cm -1 and the N-H bending vibration peak at about 1617 cm -1 weaken and shift to lower frequencies, indicating that the BMA / AM copolymer undergoes an imidization reaction during high-temperature heat treatment (as shown in Figure 1)。However, since the cyclization reaction between the side-chain ester group and the amide group can only occur when they are adjacent to each other on the molecular chain, and the proportion of alternating copolymerization of BMA and AM under thermal initiation polymerization conditions is relatively small, the number of imide rings formed in this system is low, which will reduce the heat resistance and mechanical properties of the foam. Therefore, it is necessary to crosslink and modify the BMA / AM copolymer system.
[0071] Example 1: A method for preparing a high-strength heat-resistant polymethacrylimide foam, which is specifically completed according to the following steps:
[0072] I. Weighing materials:
[0073] Weigh 50 parts by weight of butyl methacrylate, 45 parts of acrylamide, 0.2 part of initiator, 3 parts of foaming agent, and 2 parts of crosslinking agent to obtain raw materials;
[0074] The foaming agent described in step I is urea and ammonium carbonate, and the mass ratio of urea to ammonium carbonate is 3:1;
[0075] The initiator described in step I is azobisisobutyronitrile;
[0076] The crosslinking agent described in step I is ethylene glycol dimethacrylate (EDGMA);
[0077] II. Prepolymerization:
[0078] Place the raw materials in a high-temperature water bath at 90 °C for 20 min for prepolymerization to obtain a prepolymerized system;
[0079] III. Polymerization:
[0080] Adopt the casting method to pour the prepolymerized system into a closed mold with nitrogen protection, and then place the mold in a constant-temperature water bath for polymerization for 45 h. The water bath temperature is controlled at 55 °C, and the mold is removed to obtain a transparent copolymer resin sheet;
[0081] IV. Foaming:
[0082] Place the transparent copolymer resin sheet in a flat vulcanizer at 200 °C for foaming for 40 min to obtain a foam material;
[0083] V. Heat treatment:
[0084] Put the foam material into a high-temperature oven at 240 °C for heat treatment for 16 h, and then naturally cool it to room temperature to obtain a high-strength heat-resistant polymethacrylimide foam.
[0085] Example 2: The difference between this example and Example 1 is that the crosslinking agent described in step I is allyl methacrylate (AMA). Other steps and parameters are the same as those in Example 1.
[0086] Example 3: The difference between this example and Example 1 is that the crosslinking agent described in Step 1 is triallyl isocyanurate (TAIC). Other steps and parameters are the same as those in Example 1.
[0087] Figure 3 FTIR spectra of PMI foams prepared by adding different crosslinking agents. In the figure, (a) is the BMA / AM copolymer prepared without adding a crosslinking agent in Comparative Example 1, (b) is the high-strength and heat-resistant polymethacrylimide foam prepared using the EDGMA crosslinking agent in Example 1, (c) is the high-strength and heat-resistant polymethacrylimide foam prepared using the AMA crosslinking agent in Example 2, and (d) is the high-strength and heat-resistant polymethacrylimide foam prepared using the TAIC crosslinking agent in Example 3;
[0088] Analysis Figure 3 From curve (a), it can be seen that the vibration peak at a wavenumber of 1723 cm -1 is the stretching vibration peak of C=O of the BMA link in the PMI foam. The vibration peaks at wavenumbers of 1666 cm -1 and 1618 cm -1 are the stretching vibration peak of C=O and the bending vibration peak of N-H of the AM link. The double peaks at wavenumbers of 1270 cm -1 and 1240 cm -1 are the double stretching vibration peaks of C-O-C of the BMA link. The vibration peak at a wavenumber of 1145 cm -1 is the stretching vibration peak of C-O in the BMA link. Curves (b), (c), and (d) are the FTIR spectra of the BMA / AM copolymer foams added with EGDMA, AMA, and TAIC, respectively. From curves (b) and (c), it can be seen that the ester group characteristic peaks at wavenumbers of 1723 cm -1 , 1270 cm -1 , 1240 cm -1 and 1145 cm -1 are enhanced compared with curve (a). In curve (d), the stretching vibration peak of C=O at a wavenumber of 1666 cm -1 is enhanced, and the peak width is increased. This shows that all three crosslinking agents have undergone crosslinking reactions with the copolymer.
[0089] Due to the crosslinking reaction, the regions where the six-membered imide ring is not formed are connected into a crosslinked network-like three-dimensional structure, which can greatly improve the mechanical and heat-resistant properties of the copolymer foam. Under the crosslinking agent system, the polymer chain structure of PMI (taking EDGMA and AMA as examples) is as Figures 4 - 5 shown.
[0090] The compressive strength and flexural strength of the BMA / AM copolymer foam prepared in Comparative Example 1 and the high-strength and heat-resistant polymethacrylimide foams prepared in Examples 1 to 3 were tested. The specific test methods are as follows:
[0091] Compressive strength:
[0092] According to GB / T 8813-2008, standard test specimens with dimensions of 50 mm × 50 mm × 25 mm were cut from the foam board at a compression rate of 1 mm / min to measure the compressive strength of the foam material.
[0093] Flexural strength:
[0094] According to GB / T 8812-2007, standard test specimens with dimensions of 120 mm × 25 mm × 20 mm were cut from the foam board at a flexural rate of 2 mm / min to measure the flexural strength of the foam material.
[0095] The above test results are shown in Table 1;
[0096] Table 1
[0097]
[0098] Heat distortion temperature:
[0099] According to DIN 53424, standard test specimens with dimensions of 40 mm × 40 mm × 20 mm were cut from the foam board to measure the heat distortion temperature of the foam material.
[0100] The above test results are shown in Table 2;
[0101] Table 2
[0102]
[0103] As can be seen from Table 1 and Table 2, in the present invention, ethylene glycol dimethacrylate, allyl methacrylate or triallyl isocyanurate is used as a crosslinking agent, which improves the mechanical properties and heat distortion temperature of the BMA / AM copolymer foam.
[0104] Example 4: The difference between this example and Example 1 is that in Step 1, 40 parts by weight of butyl methacrylate, 55 parts by weight of acrylamide, 0.2 part of initiator, 3 parts of foaming agent and 2 parts of crosslinking agent were weighed to obtain the raw materials. Other steps and parameters are the same as those in Example 1.
[0105] Example 5: The difference between this example and Example 1 is that in Step 1, 45 parts by weight of butyl methacrylate, 50 parts by weight of acrylamide, 0.2 part of initiator, 3 parts of foaming agent and 2 parts of crosslinking agent were weighed to obtain the raw materials. Other steps and parameters are the same as those in Example 1.
[0106] Example 6: The difference between this example and Example 1 is that in step one, 45 parts by weight of butyl methacrylate, 50 parts of acrylamide, 0.2 part of initiator, 3 parts of foaming agent and 1 part of crosslinking agent are weighed to obtain the raw materials. Other steps and parameters are the same as those in Example 1.
[0107] The compressive strength, flexural strength and heat distortion temperature of the high-strength and heat-resistant polymethacrylimide foams prepared in Example 1 and Examples 4 to 6 were tested, and the test data are listed in Table 2;
[0108] Table 2
[0109]
Claims
1. A preparation method of a high-strength heat-resistant polymethacrylimide foam, characterized in that The preparation method is specifically completed according to the following steps: I. Weighing materials: Weigh 40 to 50 parts by weight of butyl methacrylate, 45 to 55 parts by weight of acrylamide, 1 to 3 parts of a crosslinking agent, 2 to 5 parts of a foaming agent, and 0.2 to 0.3 parts of an initiator to obtain raw materials; The crosslinking agent described in step I is ethylene glycol dimethacrylate, allyl methacrylate, or triallyl isocyanurate; The foaming agent described in step I is urea and ammonium carbonate, and the mass ratio of urea to ammonium carbonate is 3:1; II. Pre-polymerization: Place the raw materials in a high-temperature water bath at 80 to 95 °C for pre-polymerization for 5 to 30 minutes to obtain a pre-polymerized system; III. Polymerization: Using the casting method, pour the pre-polymerized system into a closed mold with nitrogen protection, and then place the mold in a constant-temperature water bath for polymerization for 45 to 50 hours. The water bath temperature is controlled at 40 to 60 °C. Remove the mold to obtain a transparent copolymer resin sheet; IV. Foaming: Place the transparent copolymer resin sheet in a flat vulcanizing machine at 180 to 200 °C for foaming for 30 to 60 minutes to obtain a foam material; V. Heat treatment: Put the foam material into a high-temperature oven at 200 to 280 °C for heat treatment for 8 to 24 hours, and then naturally cool to room temperature to obtain high-strength heat-resistant polymethacrylimide foam.
2. The preparation method of a high-strength heat-resistant polymethacrylimide foam according to claim 1, characterized in that The initiator described in step I is azobisisobutyronitrile.
3. The preparation method of a high-strength and heat-resistant polymethacrylimide foam according to claim 1, characterized in that In step I, weigh 45 parts by weight of butyl methacrylate, 50 parts by weight of acrylamide, 2 parts of a crosslinking agent, 3 parts of a foaming agent, and 0.2 parts of an initiator.
4. The preparation method of a high-strength heat-resistant polymethacrylimide foam according to claim 1, characterized in that In step II, place the raw materials in a high-temperature water bath at 90 to 95 °C for pre-polymerization for 10 to 20 minutes to obtain a pre-polymerized system.
5. The preparation method of a high-strength heat-resistant polymethacrylimide foam according to claim 1, characterized in that In step II, place the raw materials in a high-temperature water bath at 80 to 90 °C for pre-polymerization for 25 to 30 minutes to obtain a pre-polymerized system.
6. The preparation method of a high-strength heat-resistant polymethacrylimide foam according to claim 1, characterized in that In step III, use the casting method to pour the pre-polymerized system into a closed mold with nitrogen protection, and then place the mold in a constant-temperature water bath for polymerization for 48 to 50 hours.
7. The preparation method of a high-strength heat-resistant polymethacrylimide foam according to claim 1, characterized in that The water bath temperature described in step III is controlled at 45 to 55 °C.
8. The preparation method of a high-strength and heat-resistant polymethacrylimide foam according to claim 1, characterized in that In step IV, place the transparent copolymer resin sheet in a flat vulcanizing machine at 190 to 200 °C for foaming for 50 to 60 minutes to obtain a foam material.
9. The preparation method of a high-strength heat-resistant polymethacrylimide foam according to claim 1, characterized in that In step V, put the foam material into a high-temperature oven at 240 to 280 °C for heat treatment for 8 to 16 hours.
10. The preparation method of a high-strength heat-resistant polymethacrylimide foam according to claim 1, wherein In step V, put the foam material into a high-temperature oven at 200 to 240 °C for heat treatment for 16 to 24 hours.